Description of eleven new species of the goblin spider genus Neoxyphinus Birabén, 1953 (Araneae, Oonopidae) - Moss, Daniella F.; Feitosa, Níthomas M.; Bonaldo, Alexandre B.; Ruiz, Gustavo R. S. (Zootaxa, 2016)
The spiders of the genus Neoxyphinus Birabén differ from those of other oonopid genera by the male endites with an api-cal, retrolateral excavation bearing a subapical tooth-like apophysis and, in females, by the ellipsoid genital atrium, with angular lateral margins. In this paper, eleven new species of the genus are described, mainly from northern South America: N. amazonicus Moss & Feitosa, sp. nov. (♂♀) from Colombia and Brazil; N. macuna Moss & Ruiz, sp. nov. (♂♀), N. tuparro Moss & Ruiz, sp. nov. (♂) and N. pure Moss & Bonaldo, sp. nov. (♂♀) from Colombia; N. yekuana Moss & Feitosa, sp. nov. (♂♀), N. trujillo Moss & Bonaldo, sp. nov. (♂♀), N. yacambu Moss & Feitosa, sp. nov. (♂) and N. saarineni Moss & Bonaldo, sp. nov. (♂) from Venezuela; N. inca Moss & Ruiz, sp. nov. (♂♀) from Peru; N. beni Moss & Feitosa, sp. nov. (♂♀) from Bolivia; and N. coca Moss & Feitosa, sp. nov. (♂♀) from Ecuador.